2005
DOI: 10.1227/01.neu.0000156785.63530.4e
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Clipping of Complex Basilar Apex Aneurysms: A Strategy for Successful Outcome Using the Pretemporal Transzygomatic Transcavernous Approach

Abstract: We report the largest series of a unique, challenging group of complex basilar apex aneurysms treated with the pretemporal transzygomatic transcavernous approach, which provided improved safety of clipping by 1) increased visualization of the basilar apex and perforator arteries, 2) improved maneuverability of clip application, 3) a safer perforator-free location, and 4) preservation of brainstem collateral flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 47 publications
1
62
0
5
Order By: Relevance
“…This may be due to the greater durability of microsurgery compared with embolization. A previous study reported that clipping was successful in 95% of patients with complex basilar top aneurysms, with no evidence of residual aneurysms on follow-up angiography provided 14,15) . Radiological complete occlusion of basilar apex aneurysms in our series was relatively worse than previous report.…”
Section: Features Of Microsurgical Clippingmentioning
confidence: 96%
“…This may be due to the greater durability of microsurgery compared with embolization. A previous study reported that clipping was successful in 95% of patients with complex basilar top aneurysms, with no evidence of residual aneurysms on follow-up angiography provided 14,15) . Radiological complete occlusion of basilar apex aneurysms in our series was relatively worse than previous report.…”
Section: Features Of Microsurgical Clippingmentioning
confidence: 96%
“…Their higher morbidity has encouraged different surgical and endovascular approaches; nevertheless, treatment is still fraught with limitations, especially intraoperative and postoperative morbidity and, with endovascular methods, high rates of incomplete occlusion and late reopening 1,2,3,4,5,6,7,8,9,10 . Several series have reported the outcomes of patients undergoing surgical or endovascular treatment of basilar aneurysms 9,27 .…”
Section: Basilar Artery Aneurysms Account For Approximately 7%mentioning
confidence: 99%
“…In patients afflicted with any of the aforementioned aneurysms, intraoperative extra-or intradural removal of the ACP (anterior clinoidectomy) is an essential manoeuvre to expose the aneurysm neck in order to ensure safe clip placement. Likewise, treatment of some supraclinoid aneurysms, basilar artery aneurysms, giant pituitary adenomas, and cavernous sinus lesions also require an anterior clinoidectomy, which is an important step in an extended neurosurgical approach [1,3,12,14,23,24]. In cases of suprasellar meningiomas, recurrent growth is prevented by removal of the bony tumour origin, including the ACP; therefore, an anterior clinoidectomy is also used in the treatment of such patients.…”
Section: Introductionmentioning
confidence: 99%